Civil Liability of Wedding Organizers toward Vendors and Customers for Acts of the Organizing Committee - Karina Putri; Subekti Subekti; M.Yustino Aribawa (Penerbit Goodwood, 2026)
Purpose: This study aims to examine the forms and scope of the civil liability of wedding organizers toward third-party vendors and customers resulting from the actions of the organizing committee, and to develop a civil liability framework that provides legal certainty while ensuring balanced legal protection for all parties involved.Research Methodology: This study adopts a qualitative approach using a normative juridical research method. The analysis is based on an extensive literature review of statutory regulations and national and international scholarly publications published within the last five years, supplemented by illustrative scenarios drawn from publicly reported patterns of wedding organizer disputes, used solely to contextualize the legal analysis rather than as a formal empirical dataset.Results: The findings indicate that the civil liability of wedding organizers is primarily based on breach of contract, tort, and the principle of vicarious liability. Negligent acts committed by the organizing committee remain the responsibility of the wedding organizer insofar as they occur within the scope of their assigned duties. Financial transparency and effective internal governance constitute the primary preventive measures for minimizing the risk of legal disputes.Conclusions: Wedding organizers bear the primary contractual responsibility toward both customers and vendors. An ideal liability model should incorporate comprehensive contractual provisions, effective supervision, and an accountable financial management system.Limitations: This study is limited by its reliance on a normative legal approach and secondary data sources, without incorporating primary data obtained through direct interviews with the parties involved.Contributions: This study contributes theoretically to the development of the doctrine of vicarious liability in project-based service industries and provides practical contributions to the establishment of contractual standards for the wedding organizer industry.